CONTINUING EDUCATION FOR EMPLOYEES OF THE ETHICS COMMITTEE (International Seven Journal of Multidisciplinary, 2025)
Since 2000, the Gaspar Vianna Hospital de Clínicas Foundation has implemented a continuing education program for the members of the Research Ethics Committee. In 2024, the annual action plan was updated in accordance with operational standard 001/2013.Objective To train the members of the Committee in order to improve the quality of the rapporteurships. Experience report on the creation of a hybrid course with one-hour monthly classes, started in February and scheduled to end in December 2024. So far, four classes have been held, addressing topics such as research ethics, pending Resolutions No. 466/2012 and 510/2016, and protocol documentation. Final thoughts: Feedback from attendees has been positive, highlighting the interaction and quality of the content. Continuing education proves to be a successful experience, contributing to the protection of research participants and the improvement of reporting.